Analisis Perubahan Batimetri Di Perairan Matras Kabupaten Bangka - Ayinah, Afi; Pamungkas, Aditya; Akhriyanti, Irma (Universitas Bangka Belitung, 2025)
Matras Beach is one of the beaches in the Bangka Belitung Islands which is used as a tourist spot. A bathymetric map is a spatial data that contains depth information (bathymetry information) for a water area. This study aims to determine changes in bathymetry in the 2015, 2019 and 2021 timeframes. The method used in this study is a descriptive method with a purposive sampling data collection technique including primary data and secondary data. The results showed that in 2015-2019 the total change in depth that occurred at the cross section line was an average of 0.805 m and an average total shallowing of 0.165 m. In 2019-2020 the total depth change that occurred was an average of 7.145 m and an average total shallowing of 0.492 m. This change causes the formation of crevices around the breakwater (area A) and around the sea (area B) caused by tin mining.